The Imprecatory Psalms in the Liturgy of the Hours after the Second Vatican Council: Reform, Reception and the Current State of the Debate - Węgrzyniak, Wojciech (Verbum Vitae, 2022)
Since 1970, the Catholic Church has not used the so-called imprecatory Psalms and verses in the Liturgy of the Hours (in total, 122 verses have been removed). This article aims to analyze the presence of controversial fragments of the Psalms in the liturgy. It consists of four parts. First, it presents the history of the process that began during the Second Vatican Council and led to the decision to remove such fragments from the liturgy. What follows, is an overview of the reception and opinions on the imprecatory Psalms over the past fifty years. The next part of this study collects arguments in favor of removing the questionable texts from the liturgy as well as an argument in favor of keeping them in it. The article concludes with an appendix of all the texts from the Book of Psalms that have been removed from the Liturgy of the Hours. The author is personally in favor of leaving the unwanted verses in the liturgy.